2000
DOI: 10.1152/ajpregu.2000.279.2.r704
|View full text |Cite
|
Sign up to set email alerts
|

Taurine secretion in primary monolayer cultures of flounder renal epithelium: stimulation by low osmolality

Abstract: Transepithelial taurine fluxes determined in short-circuited monolayer cultures of flounder renal proximal cells in Ussing chambers revealed net taurine secretion. Both unidirectional secretory and reabsorptive taurine fluxes exhibited saturation kinetics contributed by two distinct saturable transepithelial taurine transport systems operating at different taurine concentration ranges. The taurine secretory system operating below 0. 5 mM had lower affinity but higher capacity than the reabsorptive system, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Therefore, the hypotonically activated taurine transport pathways are distributed in a polarized way in gill cells. Similar findings have been observed in goldfish renal cells (14) and in amphibian A6 cells (51) but not in flounder renal cells (7). The increased gill secretion of taurine through the apical membrane in a diluted environment will help the fish excrete any excess of osmotically active material and obligated water more rapidly, thus facilitating the RVD, as observed by Benyajati and Renfro (7) in flounder renal tubules.…”
Section: Taurine Permeability Of Basolateral Membrane Increases Durinsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, the hypotonically activated taurine transport pathways are distributed in a polarized way in gill cells. Similar findings have been observed in goldfish renal cells (14) and in amphibian A6 cells (51) but not in flounder renal cells (7). The increased gill secretion of taurine through the apical membrane in a diluted environment will help the fish excrete any excess of osmotically active material and obligated water more rapidly, thus facilitating the RVD, as observed by Benyajati and Renfro (7) in flounder renal tubules.…”
Section: Taurine Permeability Of Basolateral Membrane Increases Durinsupporting
confidence: 84%
“…Investigators have reported that physiological concentrations of plasma taurine increased from 0.1-0.8 mM to 1.3-2.5 mM when marine fish were transferred from isosmotic to hyposmotic conditions (7). We suggest that the high rate of taurine secreted into the circulation (i.e., at the basolateral side) may contribute to the restoration of plasma osmotic pressure in fish, but this effect will need to be further investigated.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Taurine efflux was also found to be important in the RVD response of many other models, e.g. in teleost heart ventricular cells (Vislie, '83), dogfish shark ( S. acanthias ) rectal gland cells (Ziyadeh et al, '88), trout hepatocytes (Michel et al, '94), goldfish renal proximal tubules (Fugelli et al, '95), winter flounder ( Pleuronectes americanus ) renal cells (Benyajati and Renfro, 2000), walking catfish ( Clarias batrachus ) liver (Goswami and Saha, 2006), and sea bass gill cells (Avella et al, 2009). Regulation of taurine release includes control by external Ca 2+ (trout hepatocytes; gill cells, goldfish proximal renal tubules) and prostaglandin synthesis (Fugelli et al, '95), but further characterization of control mechanisms still awaits investigation.…”
Section: Regulatory Volume Decrease In Fish Cellsmentioning
confidence: 99%
“…In marine habitats, for example, a diverse group of organisms such as algae, oysters, mussels, copepods, diatoms, vestimentiferan worms and flounder utilize taurine as an osmolyte (Benyajati & Renfro, 2000;Burton & Feldman, 1982;Jackson et al, 1992;Pierce et al, 1992;Sansone et al, 1987;Walther, 2002;Yin et al, 2000). While sulfonate compounds are found in many environments, many eukaryotic organisms are unable to attack the carbonsulfur bond.…”
Section: Introductionmentioning
confidence: 99%